Low-Cost and Highly Sensitive Pressure Sensor with Mold-Printed Multi-Walled Carbon Nanotubes Dispersed in Polydimethylsiloxane - Tim Mike de Rijk; Walter Lang (Sensors, 2021)
Flexible pressure sensors with piezoresistive polymer composites can be integrated into elastomers to measure pressure changes in sealings, preemptively indicating a replacement is needed before any damage or leakage occurs. Integrating small percentages of high aspect ratio multi-walled carbon nanotubes (MWCNTs) into polymers does not significantly change its mechanical properties but highly affects its electrical properties. This research shows a pressure sensor based on homogeneous dispersed MWCNTs in polydimethylsiloxane with a high sensitivity region (0.13% kPa<semantics>−1</semantics>, 0–200 kPa) and sensitive up to 500 kPa. A new 3D-printed mold is developed to directly deposit the conductive polymer on the electrode structures, enabling sensor thicknesses as small as 100 μm.